(untitled) (The Research of Medical Science Review, 2025)
Background: Fluid Attenuated Inversion Recovery (FLAIR) and Diffusion Weighted Imaging are essential MRI sequences used for detection and identification of brain lesions. FLAIR is effective for visualizing lesions near CSF, while DWI is good in identifying acute ischemic stroke. This study will compare their diagnostic accuracy to know the most reliable sequence for lesion identification. Objective: The objective of this study is to compare the accuracy of DWI and FLAIR imaging in detection of brain lesions, to assess the sensitivity, and specificity of DWI and FLAIR in overall brain lesion detection and to calculate sensitivity of DWI and FLAIR for each type of brain lesion within the studied population. Method: The data was collected from Allied Hospital, Faisalabad. 106 patients’ data of age group 20 years and above and having any of the five types of brain lesions who underwent MRI brain with DWI and FLAIR was collected by using a close-ended self-modified questionnaire. Chi square, correlation, Cohn’s Kappa, sensitivity, specificity, positive predictive value and negative predictive value was also calculated between DWI and FLAIR techniques. Sensitivity and specificity of DWI and FLAIR for each type of brain lesions was also calculated. Results: The most common brain lesions detected by DWI and FLAIR was brain tumor (22.64%) and multiple sclerosis (18.86%) respectively. The most common site in which DWI and FLAIR detected most of the lesions is temporal and frontal lobe respectively. Sensitivity, specificity, positive predictive value and negative predictive value of DWI and FLAIR for overall detection of brain lesion are 83.33%, 100%, 100%, 38.46% and 56.52%, 28.57%,83.87%, and 9.09% respectively. The sensitivity of DWI and FLAIR for each type of brain lesion included in this study was also calculated separately. The result of chi square test, correlation and Cohn’s Kappa was 0.002, 1, and 1.0 respectively which shows significant results, perfect correlation and agreement respectively between DWI and FLAIR protocols. Conclusion: DWI is more accurate protocol for overall detection of brain lesions. DWI showed more accurate results for detection of ischemic stroke, brain tumors and brain abscess than FLAIR. DWI and FLAIR showed equal sensitivity for hematoma. FLAIR is detected as accurate protocol for detection of multiple sclerosis.